Institutional Redesign to Strengthen the Presidential System and Government Effectiveness in Indonesia - Bisri, M. Mustofah (Journal of Constitutional and Governance Studies, 2025)
The presidential system of government in Indonesia faces various challenges, particularly the fragmentation of power between the executive and legislative branches, which hampers the effectiveness of public policy implementation. This study aims to analyze the legal challenges confronting the presidential system and explore how institutional redesign can strengthen the checks and balances mechanism between these branches. The research method employed is qualitative, utilizing a literature study approach, where data is collected from various sources, including books, scientific journals, and official documents. The findings indicate that the existing power imbalance complicates the president’s ability to implement government programs effectively, often leading to policy stagnation and inefficiency. Proposed institutional redesigns include clarifying the president’s authority, reducing dependence on the House of Representatives (DPR) for approvals, and simplifying the structure of the presidential institution to enhance operational efficiency. The discussion emphasizes the importance of inter-institutional coordination and structured institutional reform to achieve greater government stability and effectiveness. By addressing these critical issues, the proposed reforms aim to create a more responsive and accountable government that prioritizes national interests. Ultimately, this study concludes that appropriate institutional reforms can significantly strengthen the presidential system and improve governance in Indonesia, ensuring adherence to democratic principles and enhancing public trust in government institutions.